Illustrated Catalogue of Cotton Machinery - Howard & Bullough American Machine Company (Salt Lake City, UT : Project Gutenberg, 2011)
"Illustrated Catalogue of Cotton Machinery" by Howard & Bullough American Machine Company Ltd. is a technical and industrial publication written in the early 20th century. This catalogue provides a comprehensive overview of the various machinery and equipment used in cotton processing, including machines for opening, picking, carding, drawing, and spinning cotton. It is designed to serve as a resource for cotton mill operators, detailing the capabilities and specifications of each machine. At the start of the catalogue, the introduction emphasizes the importance of the opening and picking processes in cotton production, which are often overlooked compared to carding and spinning. The narrative outlines key information about the machinery being presented, highlighting their features, advantages, and performance metrics. The opening section discusses the Hopper Bale Opener, showcasing its ability to efficiently handle and process large quantities of cotton while minimizing labor costs and improving end-product quality. This initial segment sets the tone for a detailed guide, blending technical specifications with practical applications and best practices for operating cotton machinery effectively. (This is an automatically generated summary.)
Release date is 2011-12-14
Produced by Don Kostuch
Keywords: Howard & Bullough American Machine Company -- Catalogs; Textile machinery industry -- Catalogs; Textile machinery -- Catalogs; Cotton machinery industry -- Catalogs; Cotton machinery -- Catalogs